Involving end-users in the design of an audit and feedback intervention in the emergency department setting - a mixed methods study - Welmoed K. van Deen; Edward S. Cho; Kathryn Pustolski; Dennis Wixon; Shona Lamb; Thomas W. Valente; Michael Menchine (BMC, 2019)
Abstract Background Long length of stays (LOS) in emergency departments (ED) negatively affect quality of care. Ordering of inappropriate diagnostic tests contributes to long LOS and reduces quality of care. One strategy to change practice patterns is to use performance feedback dashboards for physicians. While this strategy has proven to be successful in multiple settings, the most effective ways to deliver such interventions remain unknown. Involving end-users in the process is likely important for a successful design and implementation of a performance dashboard within a specific workplace culture. This mixed methods study aimed to develop design requirements for an ED performance dashboard and to understand the role of culture and social networks in the adoption process. Methods We performed 13 semi-structured interviews with attending physicians in different roles within a single public ED in the U.S. to get an in-depth understanding of physicians' needs and concerns. Principles of human-centered design were used to translate these interviews into design requirements and to iteratively develop a front-end performance feedback dashboard. Pre- and post- surveys were used to evaluate the effect of the dashboard on physicians' motivation and to measure their perception of the usefulness of the dashboard. Data on the ED culture and underlying social network were collected. Outcomes were compared between physicians involved in the human-centered design process, those with exposure to the design process through the ED social network, and those with limited exposure. Results Key design requirements obtained from the interviews were ease of access, drilldown functionality, customization, and a visual data display including monthly time-trends and blinded peer-comparisons. Identified barriers included concerns about unintended consequences and the veracity of underlying data. The surveys revealed that the ED culture and social network are associated with reported usefulness of the dashboard. Additionally, physicians' motivation was differentially affected by the dashboard based on their position in the social network. Conclusions This study demonstrates the feasibility of designing a performance feedback dashboard using a human-centered design approach in the ED setting. Additionally, we show preliminary evidence that the culture and underlying social network are of key importance for successful adoption of a dashboard.